2017
DOI: 10.1016/j.cellimm.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody binding to the macrophage-specific receptor sialoadhesin alters the phagocytic properties of human and mouse macrophages

Abstract: Sialoadhesin (Sn) is a surface receptor expressed on macrophages in steady state conditions, but during inflammation, Sn can be upregulated both on macrophages and on circulating monocytes. It was shown for different species that Sn becomes internalized after binding with monoclonal antibodies. These features suggest that Sn is a potential target for immunotherapies. In this study, human and mouse macrophages were treated with anti-Sn monoclonal antibodies or F(ab') fragments and the effect of their binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For example, if CD169 exists in a molecular complex with other molecule(s) required for pneumococcal uptake by macrophages, antibodies directed to CD169 could block their function through steric effects. It has also been demonstrated that under some circumstances antibodies to CD169 can trigger endocytosis and non-specifically affect phagocytosis of latex beads and bacteria37. Nevertheless, the message of the studies reported here is that pneumococcal interaction with CD169+ macrophages in the spleen can be a critical precursor of septicaemia and sepsis.…”
Section: Discussionmentioning
confidence: 64%
“…For example, if CD169 exists in a molecular complex with other molecule(s) required for pneumococcal uptake by macrophages, antibodies directed to CD169 could block their function through steric effects. It has also been demonstrated that under some circumstances antibodies to CD169 can trigger endocytosis and non-specifically affect phagocytosis of latex beads and bacteria37. Nevertheless, the message of the studies reported here is that pneumococcal interaction with CD169+ macrophages in the spleen can be a critical precursor of septicaemia and sepsis.…”
Section: Discussionmentioning
confidence: 64%
“…We observed an age-associated low bone mass phenotype in male CD169-KO mice. While CD169 has not been directly implicated in contributing to bone biology or skeletal homeostasis, it does contribute to macrophage phagocytic function (78) and cell-cell adhesion (79) . Therefore, there is the potential for CD169 to participate in osteomac support of both osteoclasts and osteoblasts (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell lysis was performed with ACK buffer for 3 mim. Bone marrow cells were incubated in a petridish with 10 mL RPMI-1640 culture medium (Gibco R , Life Technologies) enriched with 1% non-essential amino acids, 1% penicillin/streptomycin, 1% sodium pyruvate, 1% L-glutamine, 10% iFCS and 15% L929 cell line supernatant containing macrophage colony stimulating factor (M-CSF) for 6 days at 37 • C and 5% CO 2 (17). On the fourth day of incubation, bone marrow-derived macrophages were either or not stimulated with 50 IU/mL (for assessing dose-dependency) or the standard dose of 5.0 × 10 2 IU/mL IFN-α (PBL Assay Science, 12100) in a 10 mL petri dish.…”
Section: In Vitro Infections In Bone Marrow-derived Macrophagesmentioning
confidence: 99%
“…Type I IFN is known to trigger the expression of various so-called interferonstimulated genes (ISGs) (13), including some that are involved in viral recognition and entry. Sialoadhesin (Sn, CD169, Siglec-1) is an ISG-gene product (14)(15)(16)(17) expressed on macrophages, belonging to the Siglec (sialic acid binding Ig-lectin) family (18). Human and mice Sn share 72% sequence homology (19,20) and, unlike other Siglecs, seem to lack tyrosine-based signaling motifs which suggests a primary role in cell-cell interactions rather than in cell signaling (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation